Delayed anterior segment complications after the treatment of retinopathy of prematurity with laser photocoagulation - Ajjarapu, Aparna; Dumitrescu, Alina (Frontiers in Ophthalmology, 2023)
Purpose This retrospective cohort study presents a group of patients who underwent laser therapy for retinopathy of prematurity and presented with delayed anterior segment complications. Methods The charts of infants treated with laser photocoagulation for retinopathy of prematurity at our institution between 1988 and 2020 were reviewed. The data extracted included demographics, treatment and clinical examination findings, and those on visual acuity, surgical procedures, and cycloplegic refraction. The inclusion criteria were documented anterior segment changes during the follow-up period. The exclusion criteria were any prior intraocular surgery or inflammation before signs of anterior segment complications developed. The exposure was laser photocoagulation for retinopathy of prematurity and the main outcomes were anterior segment complications, visual acuity, and cycloplegic refraction. Results A total of 183 charts were reviewed. Sixteen eyes of nine patients (4.4%) met the inclusion criteria. The mean follow-up period after laser treatment was 15.9 years (range 10 years–26 years). The mean gestational age at birth was 24.6 weeks (range 23 weeks–27 weeks), and the mean age at first clinical documentation of anterior segment complications was 8.7 years (range 1 years–25 years). The complications included cataract (n = five patients/eight eyes) and glaucoma (n = three patients/five eyes), with the most frequent complication being band keratopathy (n = nine patients/15 eyes). A total of five out of 16 eyes underwent surgical procedures due to anterior segment complications. After treatment, visual acuity improved back to its baseline value in four out of five of the treated eyes, and improved, but not to its baseline value, in one out of five of the treated eyes. All the patients developed progressive high myopia over the follow-up period. Conclusions Anterior segment complications after laser photocoagulation for retinopathy of prematurity may develop later in life. They affect patients’ visual acuity and quality of life and may require treatment.